PERBANDINGAN KONDISI FISIK EKSTRAKURIKULER FUTSAL PUTRA SMKN 7 SURABAYA DAN SMAN 1 WONOAYU - ali fathoni, muhammad; HAFIDZ, ABDUL (Jurnal Prestasi Olahraga, 2019)
Tujuan penelitian adalah untuk mengetahui seberapa besar perbedaan yang signifikan antara siswa SMKN 7 Surabaya dan SMAN 1 Wonoayu dalam tes kecepatan, kelincahan, daya tahan dan daya ledak otot tungkai. Jenis penelitian yang digunakan adalah non-eksperimen dengan pendekatan kuantitatif. Sampel pada penelitihan ini adalah siswa yang mengikuti ekstrakulikuler di SMKN 7 Surabaya berjumlah 20 siswa dan SMAN 1 Wonoayu Sidoarjo berjumlah 20 siswa. pengambilan data pada penelitian ini menggunakan tes kecepatan berupa sprint 30 meter, kelincahan berupa T-Test, daya tahan berupa VO2max dan daya ledak otot tungkai berupa long jump. Hasil penelitian ini yaitu pada uji T dari keempat tes yaitu kecepatan, kelincahan, daya tahan dan daya ledak otot tungkai. Keempat tes ini memiliki hasil yang berbeda yaitu kecepatan dan kelincahan memiliki nilai yang sama yaitu sig (2-tailed) 0.000 < (sig) 0.05, maka Ho ditolak dan Ha diterima dan dapat disimpulkan ada perbedaan yang signifikan antara siswa SMKN 7 Surabaya dan SMAN 1 Wonoayu. Sedangkan daya tahan dan daya ledak otot tungkai tidak ada perbedaan yang signifikan. Jadi terdapat perbedaan yang signifikan antara kecepatan dan kelincahan antara siswa SMKN 7 Surabaya dan SMAN 1 Wonoayu. Dan tidak terdapat perbedaan yang signifikan antara daya tahan dan daya ledak otot tungkai antara siswa SMKN 7 Surabaya dan SMAN 1 Wonoayu. Kata kunci : Kondisi Fisik, Kecepatan, Kelincahan, Daya Tahan, Daya Ledak Otot Tungkai Physical condition is a very important element in almost all sports. Therefore exercise physical conditions need to get serious attention carefully planned and systematically so that the level of physical fitness and functional abilities of the bodys instruments is better. The futsal sport requires players to run, feed the ball quickly, rotate or move positions, kick the ball hard and aim and demand endurance. Besides that playing futsal is also required to be clever in tactics. The aim of the study was to find out how much a significant difference between students of SMAN 1 Wonoayu and students of Vocational High School 7 Surabaya in testing the speed, agility, endurance and explosive power of the leg muscles. The type of research used is non-experimental with a quantitative approach. The sample in this study was 20 students who attended extracurricular activities at SMAN 1 Wonoayu and 20 students from Surabaya 7 Vocational High School. Data collection in this study used a speed test in the form of a 30 meter sprint, agility in the form of T-Test, resistance in the form of VO2max and leg muscle explosive power in the form of a long jump. The results of this study are in the T test of the four tests namely speed, agility, endurance and explosive power of the leg muscles. The four tests have different results, namely speed and agility have the same value, namely sig (2-tailed) 0.000 <(sig) 0.05, then Ho is rejected and Ha is accepted and it can be concluded there are significant differences between SMAN 1 Wonoayu students and Vocational High School students 7 Surabaya. While the endurance and explosive power of the leg muscles were not significantly different. So there is a significant difference between speed and agility between SMAN 1 Wonoayu students and 7 Vocational High School students in Surabaya. And there is no significant difference between endurance and explosive power of limb muscles between students of SMAN 1 Wonoayu and students of SMK 7 Surabaya. Keywords: Physical Condition, Speed, Agility, Endurance, Explosive Power of Leg Muscles